2020
DOI: 10.1186/s12968-020-00634-y
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and feasibility of non-contrast adenosine stress cardiovascular magnetic resonance T1 mapping in patients on haemodialysis

Abstract: Background Identifying coronary artery disease (CAD) in patients with end-stage renal disease (ESRD) is challenging. Adenosine stress native T1 mapping with cardiovascular magnetic resonance (CMR) may accurately detect obstructive CAD and microvascular dysfunction in the general population. This study assessed the feasibility and reliability of adenosine stress native T1 mapping in patients on haemodialysis. Methods The feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
4
3
0
1
Order By: Relevance
“…We note that, while our resting T1 values are in line with those from other studies done on a 3 T system, 26,62 our changes in T1 from rest to stress (1.3% at the 4× adenosine dose, Table 1) are lower than what others have reported (2.8‐6.2%) 26,29,49 . Similarly, when using a conversion factor derived from Nickander et al, where a 34.4% change in MBV corresponded to a 6.2% change in T1, 29 our measured T1 values equate to an MBV increase of 7.31% at the 4× adenosine dose (Table 6), whereas other studies using systemic adenosine infusion reported increases of 30‐34% 29,52 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We note that, while our resting T1 values are in line with those from other studies done on a 3 T system, 26,62 our changes in T1 from rest to stress (1.3% at the 4× adenosine dose, Table 1) are lower than what others have reported (2.8‐6.2%) 26,29,49 . Similarly, when using a conversion factor derived from Nickander et al, where a 34.4% change in MBV corresponded to a 6.2% change in T1, 29 our measured T1 values equate to an MBV increase of 7.31% at the 4× adenosine dose (Table 6), whereas other studies using systemic adenosine infusion reported increases of 30‐34% 29,52 .…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting to note that in humans adenosine stress increases HR, 29,48–50 but pre‐clinically some studies report a decrease 8,51 similar to ours (Supporting Figure 2D,E), while others describe an increase 5,50,52 . This difference is not species specific, but instead may be caused by the anesthesia: studies using injectable anesthetics describe increased HR, while studies using inhaled anesthesia report a decrease in HR.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study at 3.0 T in patients on hemodialysis reported a mean native T1 reactivity of 3.01% in regions with normal wall motion and 1.6% in hypokinetic regions (MOLLI; adenosine: 140-210 μg/kg/min, 3 min). 41 The results in the latter study are descriptive, and the presence of advanced kidney disease in this patient population limits direct comparison of the native T1 reactivity, which may be affected by underlying microvascular dysfunction. However, the results support the use of wall motion to distinguish between normal and pathologic myocardial tissue and demonstrate applicability at a comparable magnet strength used in our study.…”
Section: Rocs Of Native and Fe T1 Reactivitymentioning
confidence: 85%
“…Advantages of both native mapping and feature tracking could relate to the possibility of achieving a sensitive, noninvasive, quantitative measure of myocardial ischemia and tissue alterations, even without the need for contrast agents, which is desirable due to increasing age and frequent concomitant renal disease in CAD patients. Poli et al have tested the feasibility and reliability of noncontrast adenosine S-CMR T1 mapping in 58 patients under haemodialysis treatment and proved excellent test-retest reliability of rest and stress native T1 [ 80 ].…”
Section: Advanced Diagnostic and Prognostic Goals For Stress Cmrmentioning
confidence: 99%